A Systematic Review and Meta-Analysis on the Safety of Antiplatelet Discontinuation Following Stent-Assisted Coil Embolization for Cerebral Aneurysms - Mohammed Maan Al-Salihi; Maryam Sabah Al-Jebur; Ahmed Abd Elazim; Ram Saha; Ahmed Saleh; Farhan Siddiq; Ali Ayyad (NeuroSci)
Background: Stent-assisted coil embolization (SACE) is a common endovascular technique for managing intracranial aneurysms. The permanent presence of a stent inside the cerebral artery necessitates the postoperative use of antiplatelets. However, a consensus about how long to continue on it remains debated. This systematic review aims to discuss and quantify the risk of ischemic complications after antiplatelet discontinuation following SACE. Methods: PubMed, Cochrane Library, Scopus, and Web of Science (WOS) were systematically searched for studies assessing the outcomes after antiplatelet discontinuation following SACE for cerebral aneurysms. The primary outcome was the odds of ischemic complications after antiplatelet discontinuation. Using a random-effects model, the pooled event rate, along with a 95% confidence interval (CI), was calculated. The Comprehensive Meta-Analysis software (CMA) software was used for the analysis. The Newcastle–Ottawa Scale (NOS) was used for the quality assessment. Results: A total of five observational cohort studies were included in this systematic review. The studies recruited cases from 2009 and 2020, predominantly in Korea and Japan. Data from 18,425 cases obtained from four studies were analyzed. The duration of antiplatelet therapy varied widely across the included studies. Additionally, most studies reported a median follow-up of 24 months or more after antiplatelet discontinuation. We extracted and analyzed the odds of thromboembolic complications occurring within 6 to 24 months after the discontinuation of antiplatelets. The pooled rate of thromboembolism after antiplatelet discontinuation in this meta-analysis was 0.01 (95% CI: 0.006 to 0.018). Conclusion: This review demonstrates that the risk of thromboembolic complications after discontinuing antiplatelet therapy post-SACE is low. However, no strong consensus exists on the ideal duration for maintaining dual- or single-antiplatelet therapy. Further prospective studies with longer follow-ups are warranted to clarify the optimal durations needed to balance thromboembolic risk with hemorrhagic complications.